BENTUK NYATA KASIH ALLAH MELALUI INKARNASI YESUS KRISTUS BERDASARKAN PANDANGAN ST. ATHANASIUS DARI ALEXANDRIA - Zai, Gunawan Christianto; Wijaya, Hendi (Sekolah Tinggi Teologi Injili Abdi Allah, 2024)
St. Athanasius of Alexandria was a Christian theologian and church father from the city of Alexandria. St. Athanasius stated that God manifested Himself in a human body through the incarnation so that His love and goodness could be a proof of salvation for mankind. St. Athanasius also said that the incarnation means that God took on fully human flesh and was present among mankind to show His power and save mankind from the power of sin. St. Athanasius also believed that Christ is the Son of God who came into the world by taking the body of an immaculate virgin, to reveal Himself to mankind. St. Athanasius' various statements make the author interested in answering that the incarnation of Jesus is one of God's actions to restore damaged human nature based on St. Athanasius' view. The method used in this research is a research method with a qualitative research approach and a literature study research type. The author collects and analyzes materials and sources in the form of books, journal articles, the Bible and other supporting sources related to the topic of this research. The author also presents the definition of God's love (saving man), the incarnation: making man return to God and Jesus Christ revealing Himself as the Son of God. The results of this study show that man's actions that violate God's commandments cause man to sin, separate from God and his nature becomes corrupted. Man could not save himself, so God, who is steadfast love, revealed and demonstrated His power by giving His only Son to incarnate and become like man to save all mankind from sin through His death and resurrection. Thus, the incarnation of Jesus was one of God's actions to restore the corrupted nature of mankind, in accordance with the view of St. Athanasius.